Protective Effect of Sumac and Terebinth Extracts Against the Negative Effects of Breast Cancer on Cardiac Tissues of in Rats - Erişir, Figen Erdem; Aydın, Sevinç; Tuzcu, Zeynep; Yılmaz, Ökkeş (Universidad del Zulia, Facultad de Ciencias Veterinarias, 2025)
Due to the toxic side effects of chemotherapeutic drugs used in breast cancer, interest in medicinal plants has increased in order to develop alternative cancer drugs. The experimental model of this study was created to observe the remedial impacts of the Terebinth (Pistacia terebinthus L.) and the Sumac (Rhus coriaria L.) plants against the negative effects of 7,12-Dimethylbenz[a]anthracene induced breast cancer on cardiac tissues in rats. For this purpose, the levels of malondialdehyde were analyzed the indicator of the oxidative stress breast cancer will cause on cardiac tissues, the catalase, glutathione transferase and superoxide dismutase enzymes, glutathione, which holds and important place among antioxidant impacts and proteins. At the end of the study, it was determined that there was an increase in malondialdehyde levels, a decrease in glutathione and protein amounts, and a decrease in antioxidant enzyme levels in rats treated with cancer-induced 7,12-Dimethylbenz[a]anthracene.
Efecto protector de los extractos de zumaque y terebinto contra los efectos negativos del cáncer de mama en los tejidos cardíacos de ratas
Keywords: Antioxidant; Antioxidante; Breast Cancer; Cardiac; Cardíaco; Cáncer De Mama